Impact of COVID-19 on lifestyle and financial behaviour: The implications to research in financial vulnerability - Ma, Ning; Siu, Yam Wing; Cheong, Tsun Se; Tung, Brian (Frontiers in Psychology, 2022)
The outbreak of coronavirus pandemic in late 2019 posted unprecedented social-economic challenges and disruptions to societies and individuals. The “new-normal” styles of living and working could intertwined with other determinants complicating the investigation of individual’s financial vulnerability. The purpose of this paper is to conduct literature survey to review and consolidate the recent scattered literatures to identify some possible factors to be considered in the research related to financial vulnerability, including pandemic’s impact of COVID-19 to different aspects of personal finance issues, pandemic-driven digitisation of the economy activities, changes in financial behaviour and addiction to digital technology.